الحق في التعليم في ضوء القانون الفلسطيني والإتفاقيات الدولية - علاونة ., فادي (University of Eloued جامعة الوادي, 2023)
ملخص: تناول هذا البحث والذي موضوعه الحق في التعليم في ضوء القانون الفلسطيني والإتفاقيات الدولية موضوع الجوانب القانونية للحق في التعليم في الأراضي الفلسطينية، فقد تم تقسيم البحث الى مبحثين تناول الأول منهما موضوع الحق في التعليم في ضوء الشرعة الدولية، وتم تحديد النصوص القانونية في المعاهدات الدولية وخصوصا الاعلان العالمي لحقوق الإنسان، والعهد الخاص بالحقوق الاقتصادية والاجتماعية والثقافية، إضافة الى دور بعض المنظمات الدولية في تكريس هذا الحق بشكل عام وفي الاراضي الفلسطينية بشكل خاص. كما تم الحديث وفي المبحث الثاني عن الحق في التعليم في ضوء القوانين الفلسطينية، فقد تم الحديث عن هذا الحق في القانون الأساسي الفلسطيني، وفي القرار بقانون الخاص بالتعليم العالي الفلسطيني، وتم تحليل هذه النصوص للوصول الى الهدف الأساسي من هذا البحث وهو كيف عالجت القوانين الفلسطينية موضوع الحق في التعليم. وقد توصل البحث الى مجموعه من التوصيات أهمها، ضرورة إصدار قانون للتعليم ينظم الشؤون التعليمية في المراحل الأساسية والابتدائية والثانوية يتلاءم مع التحديث في العمليات التعليمية الحالية، والعمل على تعديل القرار بقانون رقم 6 لسنة 2018 الخاص بالتعليم العالي ليتضمن نصوصا خاصة بشكل أكبر فيما يتعلق بإلزامية التعليم ومجانتيه ودور الدولة في توفيره لغير القادرين عليه. الكلمات المفتاحية: الحق ، التعليم، حقوق الإنسان، الدستور، الحريات العامة. Abstract: This research, whose topic is the right to education in the light of Palestinian law and international agreements, dealt with the legal aspects of the right to education in the Palestinian territories. The Universal Declaration of Human Rights, and the Covenant on Economic, Social and Cultural Rights, in addition to the role of some international organizations in enshrining this right in general and in the Palestinian territories in particular. The second topic, the right to education in light of Palestinian laws was also discussed. This right was discussed in the Palestinian Basic Law, and in the decree-law on Palestinian higher education. These texts were analyzed to reach the primary goal of this research, which is how the Palestinian laws dealt with the issue of the right to education. The research reached a set of recommendations, the most important of which is the need to issue an education law that regulates educational affairs in the basic, primary, and secondary stages in line with modernization in the current educational processes, and works to amend Decree-Law No. 6 of 2018 on higher education to include more special provisions with regard to compulsory schooling. It is free and the role of the state in providing it for those who are unable to do so. key words: Right, education, human rights, constitution, public freedoms.
The Right Of Education In Palestinian Law And International Conventions Small Letters
المجلد 14 العدد1
Keywords: لحق ، التعليم، حقوق الإنسان، الدستور، الحريات العامة.; Right, education, human rights, constitution, public freedoms